Developing Dynamic Innovative Capabilities: The Growing Role of Innovation and Learning in the Development of Organisations and Skills in Developed and Emerging Nations of Europe. Issue 1 (January 2015) - Makó, Csaba; Mitchell, Brian; Illéssy, Miklós
The concepts of 'high performance working system' (HPWS) and lean production represent the theoretical and methodological foundations of this article. We make a distinction between three theoretical strands of the HPWS and the lean production approaches, namely: ( i ) the diffusion of the Japanese-style management and organisational practices both in the US and in the Europe (Aoki, 1990; Ramsay, Scholarios and Harley, 2000; Wood, 1999); ( ii ) the approach developed by advocates of the sociology of work, which deal with the learning/innovation capabilities of new forms of organisation of work (Makó, 2005; Valeyre et al., 2009); and ( iii ) the various types knowledge and learning process and their relations with the innovation capabilities of the firm (Lam, 2005; Makó, Illéssy and Csizmadia, 2012). We develop our arguments in both spatial and temporal contexts. A micro-level analysis accompanying our macro-level enquiry enables us to illustrate the key factors driving or impeding innovation and learning at both country- and firm-specific scenarios. We carry out international comparative analysis using both employer- and employee-focused surveys to demonstrate the diffusion and outcomes of workplace innovation in knowledge-based (information and communication technology [ICT] and business services) firms. We present the results of the various waves of the employers-oriented community innovation surveys (CIS) with special focus on the periods of 'pre' and 'after' financial crises and the economic downturn. We also draw on some of the empirical lessons on the innovation/learning capabilities of the work-organisations based on the European working conditions surveys (EWCS) and the views of employees. Finally, we select the fast-growing knowledge intensive business service (KIBS) sector to illustrate the key role of workplace/organisational innovations and their drivers in two selected post-social countries: Hungary and Slovakia. The aggregated country-level data do not help us to understand the drivers and enablers of innovation. We contend that sector-focused analysis may help us to better understand the roles of these factors in the overall innovation performance of each country. For the purpose of illustration, the diffusion of organisational innovations and company knowledge development practices were analysed in the Hungarian and Slovak KIBS sector. Slovak firms had a leading position compared to the Hungarian firms implementing more radical forms of organisational innovations which were accompanied with more robust learning practices. Drivers explaining this variety were the degree of countries' involvement (embedding) in the internationalisation of the service activities and the development of networking (company group membership) process.